Association between long-term ambient air pollution exposure and the incidence of breast cancer: A meta-analysis based on updated evidence - Ruohan Wang; Peihan Wang; Yongkang Zhou; Yinan Wang; Chengdong Xu; Zhenbo Wang; Wei Wang (Ecotoxicology and Environmental Safety)
Background: Air pollution is a significant risk factor for breast cancer. However, epidemiological studies have yielded inconsistent results. Previous systematic reviews and meta-analyses have identified an association between nitrogen dioxide (NO2) exposure and the incidence of breast cancer, yet no consistent association has been observed for particulate matter (PM). With recent studies providing new evidence, updated meta-analyses are necessary. Methods: Relevant studies were identified through comprehensive literature searches in the Web of Science and PubMed databases. The pooled effect estimates for the associations of NO2, PM2.5, and PM10 with breast cancer incidence were calculated using a random-effects model. Publication bias was corrected, and sensitivity analyses were conducted to ensure the robustness of the findings. Subgroup analyses were performed based on menopausal status, hormone receptor subtype, and study region. Results: A total of 22 studies were included in this meta-analysis. The pooled hazard ratios with 95 % confidence intervals (CIs) for breast cancer incidence per 10 μg/m3 increase in NO2 and PM2.5 were 1.02 (95 % CI: 1.01, 1.03) and 1.06 (95 % CI: 1.02, 1.11), respectively. No significant association was observed between PM10 and breast cancer incidence. NO2 and PM10 exposures were significantly associated with the incidence of postmenopausal breast cancer. The associations of NO2, PM2.5, and PM10 with estrogen/progesterone receptor-positive (ER+/PR+) breast cancer were not significantly different from those with estrogen/progesterone receptor-negative (ER–/PR–) breast cancer. Exposure to both NO2 and PM2.5 was associated with breast cancer incidence in Europe, whereas in North America, only NO2 exposure showed a significant association. Conclusion: This study is the first to document a significant association between long-term exposure to ambient PM2.5 and breast cancer incidence through meta-analysis. Air pollution has a pronounced impact on postmenopausal breast cancer, and the strength of the association between specific air pollutants and breast cancer incidence varies across regions. These findings suggest that long-term exposure to NO2 and PM2.5 may increase the incidence of breast cancer.